Exploring development of smart city research through perspectives of governance and information systems: a scientometric analysis using CiteSpace. Issue 4 (25th May 2020) - Zhou, Shuling; Zhang, Xi; Liu, Juan; Zhang, Kaihua; Zhao, Yuqing
Abstract : Purpose: Smart cities show a "booming" trend both in the academia and the industry in recent years. Scholars across the world have been investigating how new technologies are applied to develop new services to the inhabitants and cities all over the world also address the "smart cities" challenges by promoting policymaking and governance. This paper aims to conduct in-depth research on smart cities by combining the study of governance policy study and information technology study. Design/methodology/approach: This paper empirically mapped the trends of smart city development, outstanding scholars and hot topics about smart cities by analyzing important references using CiteSpace. The authors visualized references and topics to analyze smart city research, based on empirical data from Web of Science. Furthermore, two most important research branches – topics from smart city governance research and those from information systems (IS) research were studied, respectively. Findings: First, the authors mapped the development of research and divided the development into three different stages. Second, the authors explored important, influential and instructive publications and publications' attributes including authors, institutions, journals and topics. Third, the authors found there are different characteristics between the IS group and the governance group in publication situations, influential institutions, journals and authors, although the research points of the two branches are overlapping and fragmented. Finally, the authors proposed important topics, which include "internet of things (IoT)", "big data", "smart city systems" and "smart city management" and the authors predicted that "IoT" and "smart city challenge" would be future trends in recent years. Originality/value: This study is an innovative research of its category because it visualized the development of smart city research, analyzed both governance and technology branches of smart city research synthetically using CiteSpace and forecasted future trends of smart city research by topics analysis and visualization of evolution.